Investigating Consumer Decision-Making Styles of Car Buyers in Croatia - Tonković Pražić, Ivana (Oeconomica Jadertina, 2021)
This research sought to explore consumer decision-making styles of buyers in the car market in the Republic of Croatia. Additional aim of this research was also to add on the literature on consumer decision-making styles to further the understanding of the specificity of consumer behavior when buying a car. The research was conducted with in-depth interviews with car buyers using a non-probability purposive sample. Furthermore, interviews were conducted with car dealership employees who were consulted for additional information. The results indicate that car buyers in the Republic of Croatia make their car buying decisions based on specific consumer decision-making styles. Based on the relevant literature and empirical research, ten consumer decision-making styles specific to car buyers in the Republic of Croatia were identified: price sensitivity, susceptibility to the influence of others, interest in automobiles, involvement in car purchase, brand loyalty, and brand, quality, aesthetics, innovation and functionality consciousness. The research was conducted on a sample of respondents from the Croatian market, so the results cannot be applied to other markets. Also, the study was conducted on a smaller and a non-representative sample, so the results should be verified on a larger and representative sample.